The Influence of Work-Life Balance and Job Competence on Employee Performance Through Job Satisfaction as an Intervening Variable - Isran Sutoyo; Dahliah Baharuddin; B. Budiandriani (Manunggal Halim Jaya, 2025)
This study aims to examine the influence of Work-Life Balance and Job Competence on Employee Performance through Job Satisfaction as an Intervening Variable at PT PLN (Persero) UP3 Bau-Bau. The data in this study were obtained from PT PLN (Persero) UP3 employees in 2025 who agreed to be respondents. This study utilized primary data collected through field research, which involved distributing questionnaires/statements to respondents. The sample was drawn using the census method due to the small sample size, as it consisted of the entire population, which totaled only 92 employees. Data analysis techniques were employed using descriptive statistical analysis and Partial Least Squares (PLS). The hypothesis test results show that Work-Life Balance has a positive and significant effect on Employee Performance. Job Competence has a positive and significant effect on Employee Performance. Job Satisfaction has a positive and significant effect on Employee Performance. Work-Life Balance has a positive and significant effect on Job Satisfaction. Job Competence has a positive and significant effect on Job Satisfaction. Work-Life Balance has a positive and significant effect on Employee Performance through Job Satisfaction as an intervening variable. Job Competence has a positive and significant effect on Employee Performance through Job Satisfaction as an intervening variable.